If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 + -3x = 6x + 24 Reorder the terms: -27 + -3x = 24 + 6x Solving -27 + -3x = 24 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -27 + -3x + -6x = 24 + 6x + -6x Combine like terms: -3x + -6x = -9x -27 + -9x = 24 + 6x + -6x Combine like terms: 6x + -6x = 0 -27 + -9x = 24 + 0 -27 + -9x = 24 Add '27' to each side of the equation. -27 + 27 + -9x = 24 + 27 Combine like terms: -27 + 27 = 0 0 + -9x = 24 + 27 -9x = 24 + 27 Combine like terms: 24 + 27 = 51 -9x = 51 Divide each side by '-9'. x = -5.666666667 Simplifying x = -5.666666667
| -81-9x=21+8x | | 10r-15s= | | 12n+3=4n-6 | | 9x^2-79x-130=0 | | 14c+28d= | | 7y+6x-3=3y-3x+2 | | n+(-20)=7-n | | 84-3x=3x+24 | | 4y+6z= | | 35-3x=2x | | 61-3x=61-3x | | 8n+24= | | 5e-5f= | | 3a-3b= | | 79-3x=2x-9 | | 12x-2=7x | | 4x^2+ab-2ax-2bx=0 | | y=5x^2-30x+20 | | (X+2)(x-4)=16 | | (4w+8)/(w^2-4w)(w^2-3w-4)/(w^2-3w+2)=0 | | 20a^3-39a^2+18a=0 | | 59-4x=10x-17 | | 6d+1=4d+7 | | 9(a+9)=104.4 | | 6x(x-5)=0 | | (5x-8)(4x-9)= | | 3x+59=8x-6 | | h=32+-16t^2 | | 2(3)-5(-4)=-10 | | 18(2m+11)= | | 13.4=3c-7 | | 4e-6=12 |